Pragmatic Analysis in Digital Communication: A Case Study of Language Use on Social Media - Kamsinah Kamsinah; Nurasia Natsir; Nuraziza Aliah (International Journal of Economics, Commerce, and Management, 2024)
This study investigates the pragmatic strategies employed in digital communication, specifically within social media platforms. As the use of social media continues to rise, understanding how users navigate language and meaning in these contexts becomes increasingly vital. Utilizing a qualitative approach, the research analyzes user interactions on platforms such as Twitter, Instagram, and Facebook to identify key pragmatic strategies, including politeness, implicature, and contextual cues. The findings reveal that social media users employ diverse strategies to convey messages effectively in an environment characterized by brevity and immediacy. Additionally, the research highlights significant cultural influences on language use, showcasing variations in communication styles, humour, and politeness norms across different cultural backgrounds. These insights underscore the importance of cultural awareness in fostering effective cross-cultural communication. Ultimately, this research contributes to the field of pragmatics by enhancing our understanding of the interplay between language, culture, and digital communication. The study also offers practical recommendations for social media users to improve their communication effectiveness, facilitating more respectful and meaningful interactions in the digital space. As digital communication evolves, further exploration of emerging trends and challenges in this area is essential for adapting to the dynamic landscape of human interaction.